Study of the dependence of the pressure of vapors of dimethylsulfoxide and perfluorinebenzene on the temperature. - V. I. Zhuchkov; A. V. Anisimov; S. A. Reshetov; P. G. Rumjantsev; A. K. Frolkova (Тонкие химические технологии, 2008)
Are obtained the experimental dependences of the pressure of the saturated vapor on the temperature for the clean of dimethylsulfoxide and perfluorinebenzene in the range of temperatures, that corresponds to extractive rectification under the atmospheric pressure.